Acute and chronic effects on central hemodynamics and arterial stiffness in professional rowers - Franzen, K.; Reppel, M.; Köster, J.; Mortensen, K. (Physiological Measurement, 2016)
Controversial data exist on acute and chronic effects of competitive sports on central hemodynamics and arterial stiffness. We investigated chronic as well as acute training effects in professional rowers. The trial was planned as a non-randomized, controlled pilot-study comparing athletes and controls. 13 German national team rowers (24.1 ± 1.5 years) and 12 controls (23.8 ± 0.8 years) participated. Aortic, brachial hemodynamics and arterial stiffness were measured (Arteriograph, TensioMed®, Hungary) before and after a standardized exercise test. Chronic heart rate (49 +/- 2 bpm versus 70 +/- $ 2 bpm, p < 0.05) as well as brachial diastolic pressure (65 +/- 2 mmHg versus 74 +/- 2 mmHg, p < 0.05) was significantly lower in rowers. Physical power (305 +/- 63 versus 158 +/- 60 W, p < 0.001) was better. Chronic aortic pulse pressure (41.6 +/- 6.0 versus 35.2 +/- 3.8 mmHg; p < 0.01) and AIx (9.1 +/- 5.4 versus 7.0+/- 10.2; p < 0.01) were significantly higher in athletes. After the all-out test (acute effects) pulse wave velocity (rowers: 6.6 +/-1.2 m s-1 versus 7.8 +/- 1.6 m s-1, p < 0.001; control group 6.0 +/- 0.4 m s-1 versus 8.0 +/- 1.4 m s-1, p = 0.005) and heart rate (rowers: 49 +/- 2 bpm versus 91 +/- 3 bpm, p < 0.001; control group 70 +/- 2 bpm versus 92 +/- 4 bpm, p < 0.001) increased significantly in both groups. The controls' aortic AIx (7.0 +/- 10.2 versus 2.0 6.0; p < 0.01) decreased significantly after exercise. Professional rowers showed higher chronic aortic pulse pressure and arterial stiffness. Given the risk associated with elevated aortic pulse pressure and AIx for development of cardiovascular diseases, longterm observations of professional rowers are needed with respect to arterial stiffness and prognosis. Furthermore the acute effects need additional research.